2017
DOI: 10.4172/2329-8731.1000151
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Human Papilloma Virus in Adolescent Girls: Mother’s Knowledge, Attitude, Desire and Practice in Nigeria

Abstract: Background: Human papillomavirus is the main causative agent of cervical cancer. The HPV vaccination targets young adolescent girls that need parents' consent for medical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(27 reference statements)
2
6
1
Order By: Relevance
“…This finding however is contrary to that of some other studies which showed no significant association between sociodemographic variables and attitude of respondents towards HPV vaccine. [16172332] This study also found a significant association between respondent's knowledge of HPV vaccine and the willingness to be vaccinated ( P = 0.002), which is in accordance with other studies conducted in India and Ibadan, ( P < 0.001) and ( P = 0.007) respectively. [1722] This implies that respondents with good knowledge of HPV and its vaccine were more willing and ready to be vaccinated compared to those with poor knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding however is contrary to that of some other studies which showed no significant association between sociodemographic variables and attitude of respondents towards HPV vaccine. [16172332] This study also found a significant association between respondent's knowledge of HPV vaccine and the willingness to be vaccinated ( P = 0.002), which is in accordance with other studies conducted in India and Ibadan, ( P < 0.001) and ( P = 0.007) respectively. [1722] This implies that respondents with good knowledge of HPV and its vaccine were more willing and ready to be vaccinated compared to those with poor knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…[31] Another study among adolescents in Nigeria reported that 62% of the respondents stated expensive cost for non-uptake of HPV vaccine. [23] Similarly, a study among mothers of adolescents in Lagos state found that most (96.5%) of the respondents reported that they would want more information on HPV and its vaccine which corroborates a similar barrier in this study which reported respondents need for more information. [32] More so, a study done among female Iranian nurses reported that inadequate knowledge of HPV vaccine (26.2%) and safety concerns (41.4%) were the major reasons for unwillingness to be vaccinated,[33] which is consistent with findings in this study where respondents stated the need for more information before becoming vaccinated and safety concerns as barriers to vaccination.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…There are no official reports of HPV vaccination and cervical cancer screening in Nigeria, but research indicates less than 14% of adolescent girls had received HPV vaccine, 15,16 and less than 10% of women had cervical cancer screenings. 17,18 Of particular note, Awodele et al.…”
mentioning
confidence: 99%